gamma-Glutamylcysteine and thiosulfate are the major low-molecular-weight thiols in halobacteria. - Newton, G L (1985)
Six representative species of extremely halophilic bacteria were found to contain approximately millimolar concentrations of gamma-glutamylcysteine in the absence of significant glutathione. Thiosulfate also accumulated in the halobacteria, apparently as a major product of cysteine oxidation.